2021
DOI: 10.1039/d1na00508a
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in cellulose-based electrospun nanofibers as multifunctional materials

Abstract: Cellulose, the most abundant natural polymer, has good biocompatibility, biodegradability, and non-toxicity, which make cellulose and its derivatives promising candidates for the fabrication of multifunctional materials while maintaining sustainability and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…can be used to obtain electrospun nanostructures [5]. Due to these characteristics, the use of nanofibers and therefore electrospinning has increased in recent years, making them optimal candidates for a wide variety of applications, including tunable hydrophobicity and water adhesion, scaffolds for tissue engineering, air filtration media, controlled drug release, biosensors, textiles, wound dressings, special membranes, and antimicrobial activities [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…can be used to obtain electrospun nanostructures [5]. Due to these characteristics, the use of nanofibers and therefore electrospinning has increased in recent years, making them optimal candidates for a wide variety of applications, including tunable hydrophobicity and water adhesion, scaffolds for tissue engineering, air filtration media, controlled drug release, biosensors, textiles, wound dressings, special membranes, and antimicrobial activities [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its structure, cellulose is susceptible to considerable modifications to give rise to new derivative compounds that may be more appropriate than cellulose for certain applications [14]. There is a large variety of cellulose derivatives, such as methylcellulose, cellulose acetate, and ethylcellulose, among others, with the latter two being the most widely used [8,[14][15][16][17]. These organic compounds are obtained from cellulose, modifying its original structure by substituting external hydroxyl groups with methyl, acetyl, or ethoxy groups, respectively [12].…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the electrospinning of other cellulose derivatives are beyond the scope of this review and the reader is referred to recent detailed review articles. 44–47…”
Section: Electrospinning With Green Solventsmentioning
confidence: 99%
“…Nanopapers with a pore size of 19 nm were prepared using a vacuum filtration technique which utilized aluminum chloride (AlCl 3 ) as a coagulating agent. This coagulant considerably enhanced their permeability, making them suitable for use in UF membranes [ 63 , 64 , 65 , 66 ]. Other than that, the preparation of novel nanocellulose composite membranes with the potential of treating wastewater is carried out by vacuum filtration in the wet state, which produces polydopamine/bacterial nanocellulose film membranes with high stability and fast water transport [ 66 ].…”
Section: Recent Development In Nanocellulose-based Membranesmentioning
confidence: 99%
“…Electrospun nanocellulose exhibits a large number of isotropic pores evenly distributed among them due to its random arrangement. This characteristic makes it useful for a variety of applications [ 66 ]. A recent study on the production of cellulose acetate nanofibers via electrospinning on a wire mash demonstrated that the cellulose acetate fibers were selectively aligned vertically, horizontally, and then crossed at 45 degrees to the junction sites to create a surface template for future impregnation research.…”
Section: Recent Development In Nanocellulose-based Membranesmentioning
confidence: 99%